Metal mediated template synthesis of ligands - Costisor, Otilia (World Scientific Pub. Co., 2004)
This book surveys the relatively new area of the synthesis of organic ligands when metal ions act as a template. In the last fifty years this field has undergone an explosive development, marked by a great amount of literature. The material in the book has been arranged according to the type of chemical reaction involved. In this frame, the basic principles of metal template reactions and the shape of the molecules are considered. Designed to satisfy the demands of students, young researchers doing their PhDs, and those working in the field of coordination chemistry, the book details the role of the metal ions and the specific properties of the formed complexes. Metal Mediated Template Synthesis of Ligands offers a comprehensive analysis with wide-ranging references and provides an extensive overview of research on metal-directed organic ligands over the past five decades.